Maqashid Syariah Sebagai Tujuan Ekonomi Islam - Maulidyah, Syafrida; Putri, Rosalyta Rifany; Pandiangan, Jeniper Indah; Oktafia, Renny (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Syariah maqasid is at the core of all economic analysis, especially those dealing with issues such as poverty, wealth distribution, and economic development. One economist stressed that achieving economic goals in Islam can be done by distributing wealth fairly so that it can be enjoyed by the whole society, not just by the wealthy few. Sharia maqasid serves as a framework in building an Islamic economy, keeping economic activity in accordance with sharia principles, as well as a bridge between God's will and human aspirations. The application of maqashid sharia in daily life is hifdz mal to obtain such benefits for charity in its fiddunya wal hereafter, hifdz din (keeping religion) is a consideration recorded part of worship to Allah SWT and hifdz 'aql maintenance of purpose because insight into knowledge can improve the level of life.